(untitled) (Carte Romanze, 2020)
The essay deals with the topic of Europe’s cultural tradition, underlining the value and up-to-dateness of Curtius’ classical summa Europäische Literatur und lateinisches Mittelalter, and reflects upon some examples of the unity of european culture and some recent critical contributions.